PENGARUH EKSTRAK KULIT BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUZ) DALAM MENGHAMBAT DEGRANULASI SEL MAST DAN MENCIT PUTIH JANTAN YANG TERSENSITISASI AKTIF - Relin Yesika; Meiridha Mutiara A. (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Type I hypersensitivity reactions, also known as allergic reactions or anaphylactic reactions. The mechanism of anaphylaxis involves the release of mediators from mediator cells. The degranulation of mast cells and basophils causes an exaggerated immune response and causes the signs and symptoms of anaphylaxis. Red dragon fruit peel contains secondary metabolites such as triterpenoid flavonoids and steroids. This study was an in vitro study of the ethanol extract of red dragon fruit peel (Hylocereus polyrhizuz) on the mast cells of male white mice induced by antigen. Five variations of the concentration used are 25; 50; 100; 200; 400 µg/mL. The percentage of mast cell degranulation by red dragon fruit peel extract at concentrations of 25; 50; 100; 200 dan 400 µg/mL is 75.27; 69.05; 64.04, 56.61; 45.17; dan 27.88%. There Red dragon fruit peel extract had a significant effect in inhibiting mast cell degranulation (p<0.05).